Entrepreneurship Education and Research in the Middle East and North Africa (MENA) Perspectives on Trends, Policy and Educational Environment (Contributions to Management Science,, 2018)
This contributed volume explores and reveals the new developments, dynamics and recommendations for entrepreneurship education in the Middle East and North Africa (MENA) region. Presenting papers by respected experts in the field, it shares essential insights on the status quo of entrepreneurial education and training programs, the characteristics and motivations of early stage entrepreneurs, and the regional framework conditions in MENA. The book closes with a bibliometric perspective on the trends in the entrepreneurship research and education being developed in MENA.